Mixed‐methods study protocol for explanation of pregnant women's concerns about antenatal anomaly screening process: Designing, implementing and evaluation of intervention. Issue 6 (30th July 2021) - Khakbazan, Zohreh; Poursharifi, Hamid; Farnam, Farnaz; Hantoushzadeh, Sedigheh; Abdollahi, Parsa; Haghani, Shima; Arjmandifar, Mitra
Abstract: Aim: This study aims to investigate the concerns of Iranian pregnant women in the antenatal anomaly screening process (AASP) and propose an intervention to reduce these concerns. Design: This exploratory sequential mixed‐methods study is conducted in three stages (qualitative, intervention design and quantitative), in Tehran. Methods: A qualitative study is carried out to collect pregnant women's concerns during the AASP. Then, a two‐step procedure is implemented. In the first step (expert session), the concerns extracted in the qualitative part are prioritized. Next, the interventions used to reduce the concerns of pregnant women in the AASP are reviewed by considering the priority determined in the previous stage. The information obtained from this step is used to design intervention. Ultimately, a randomized controlled trial is used to evaluate the effectiveness of the intervention. Discussion: The results can be used for framing policies in health systems to address pregnant women's concerns in the AASP and to promote their mental health.